FILTRASI AIR KAPUR DENGAN MEMANFAATKAN KARBON KULIT BUAH KAPUK RANDU DAN ZEOLIT - Rosyidatul Munawaroh; Masturi Masturi; Ian Yulianti; Sumarli Sumarli (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
In rural areas most of people use groundwater for their daily needs. Water in the Tambakromo area, Pati, Central Java is located in the Kendeng Mountains of Limestone Mountain Northern of Central Java contains of lime which can cause problems in the long term. The objective of the research is to make filtration of water untilize of active carbon of kapok randu fruit peels and zeolite. The independent variable in this research is the composition carbon of kapok randu fruit peels and zeolite as a water filter. The dependent variable is physical properties of the water, the water content of lime (Ca(OH)2)/ TDS. The control variable is the rate of flow of water, the water diverted filter water, filter tube diameter and height of the sand. Samples used lime water has TDS 595ppm. The results of the filtration filter 1 to 5 was 557ppm, 549ppm, 467ppm, 444ppm and 585ppm. The composition of carbon filter media and zeolite influence the water filtration result. The absorption of substances dissolved in water are best shown in the filter 4 with composition of 5 cm zeolite and 10 cm carbon able to absorb 25,38% of the substances dissolved. Keywords: lime water, filtration, filter composition.